Social entrepreneurship gains ground on Canadian campuses - SHEN, ANQI (University Affairs, 2018)
An array of new programs gives students an opportunity to tackle issues of importance to their local communities.
Keywords: Canada; Libre accès; Magazine; Mise en valeur